Achieving and Maintaining Metadata Quality: Toward a Sustainable Workflow for the IDEALS Institutional Repository. Issue 7 (17th November 2017) - Stein, Ayla; Applegate, Kelly J.; Robbins, Seth
ABSTRACT: This article documents the steps taken to assess metadata errors within the IDEALS repository. It describes the workflows established to create accurate and consistent metadata, focusing especially on the batch ingest and retroactive metadata remediation processes. It also seeks to address theoretical issues surrounding the concept of metadata quality.